Exploring the Potential of ChatGPT-4o in Translation Quality Assessment - Wang, Jingjing (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The advancement of large language models (LLMs) has demonstrated significant potential in the domains of foreign language teaching and research. By evaluating two translated works of MTI students, this study discusses the application effect of ChatGPT-4o in the evaluation of human translation based on Multidimensional Quality Metrics (MQM). The research involves literary texts and non-literary texts and conducts human translations before human and ChatGPT-4o modifications. Subsequently, the versions will be evaluated and compared in accordance with MQM standards. Through the score comparison and the qualitative analysis, the results show that ChatGPT-4o demonstrates high consistency with human evaluators in evaluating translations based on the MQM method. The scores and suggested modifications significantly enhance the translation quality, particularly in terms of maintaining terminology consistency and ensuring grammatical accuracy.